The influence of Information and Communication Technologies (ICTs) on the quality of university learning - Carrasco Huamán, José Rogelio (2019)
This paper analyzes information and communication technologies (ICTs) and their important role on the quality of university education at the Department of Economics of the Universidad Nacional Mayor de San Marcos (UNMSM). To this end, university education in Latin American and European countries is studied in order to identify strengths and use them as reference points to improve the quality of education at UNMSM, especially at said department. A questionnaire, directed at 120 respondents, including professors and students of the School of Economic Sciences, is used as a data collection instrument, which is then analyzed using the Likert scale. This analysis makes it possible to determine the degree of influence ICTs have on the quality of learning at said school, as well as the benefits of implementing the identified strengths of foreign university education.